Implementasi Sistem Booking Online Berbasis Website untuk Mendukung Smart Business pada QM Photo Studio - Dede Rizal Nursamsi; Alam Alam; De Ali Farizal; Ramadhan Ariandi; Riska Raudhatul A’naini (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2026)
QM Photo Studio still conducts its service booking process manually, which leads to several issues such as scheduling recording errors, delayed confirmations, and limited access to information regarding service availability. These conditions result in suboptimal operational efficiency and reduced service quality provided to customers. Therefore, this community service program aims to develop a web-based online booking system to improve efficiency, accuracy, and integration in photography service management. The system development was carried out using a multi-layer (4-tier) architecture method, Model-View-Controller (MVC), and a Service Layer approach implemented with the Laravel framework and MySQL database. Data collection involved observation, interviews, and documentation to comprehensively identify system requirements. The developed system is designed to facilitate customers in making online service bookings, while also assisting administrators in managing schedules, services, and transactions in a more structured and real-time manner. The implementation results show that the online booking system improves the operational efficiency of QM Photo Studio, reduces the potential for recording errors, and accelerates service confirmation processes. Furthermore, the system supports digital transformation in photography business management, making services more effective, modern, and responsive to customer needs.